KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA SMP DENGAN PENDEKATAN METAPHORICHAL THINKING - Sumiati, Sumiati; Ariani, Nyayu Masyita (Jurnal Math-UMB.EDU, 2019)
This study aims to determine whether there are differences in students' understanding of mathematical concepts by using conventional metaphorical thinking and learning approaches. This research is a quasi-experimental study. This research was conducted on July 17 - August 17 2018. The population of this study was all students of class IX TI Kerkap Bengkulu North MTs. The sample of this study is class IXB as an experimental class using the approach of metaphorical thinking and class IXA as a control class with conventional learning. Research instruments include tests of understanding mathematical concepts. Data were analyzed by t test. Based on the t-test, the results of the study showed that there were differences in students' understanding of mathematical concepts in the experimental and control classes.Â Keywords: Mathematical Concept Understanding Ability, Metaphorical Thinking Approach